Knowledge Management System to Increase Sharing of Knowledge of Creative Economy Products - Hidayah, Debby Ummul; Kusuma, Tyas Pratama Puja; Nurhayati, Septi; Rachmandha, Fajri Aulia; Fadilah, Astriditiya Laila Nur (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
One of the PKK programs, namely the development of cooperative life, is a program that aims to advance cooperatives so that they can improve the economy in a village. One of the activities included in the program is creative economic activities through information technology. With the hope of being able to produce creative economic products that have added economic value. In order to manage knowledge in an organization, an appropriate mechanism is needed so that organizational goals can be achieved. The application of a knowledge management system can be a useful tool in managing knowledge for organizations. In this study, researchers focused on the problem of knowledge management in the PKK of Pamijen Village. The research problem lies in the management of knowledge of creative economic products which is considered still not optimal. Therefore, the implementation of a knowledge management system can be an appropriate solution, especially in managing knowledge about creative economic products. The system that is built later can provide convenience such as access to information, be able to capture and store knowledge, and share knowledge about creative economic products. The purpose of this study is to apply information technology in the form of a knowledge management system as a medium for sharing knowledge about creative economic products in order to achieve the cooperative life development program. The research method applied refers to the knowledge management system development life cycle (KMSLC) which has structured stages. This research produces a knowledge management system that can be accessed via the link address http://www.kms-pkkpamijen.com.